PEMBUATAN KOMPOS BOKASHI DARI LIMBAH PERTANIAN DENGAN MENGGUNAKAN AKTIVATOR EM4 DI DESA MEGATI TABANAN - I N, DIBIA; DANA, M D; TRIGUNASIH, M D; KUSMAWATI, TATIEK; SUMARNIASIH, M D SRI (Buletin Udayana Mengabdi; Vol 9 No 1 (2010): Volume 9 No.1 – April 2010, 2012)
ABSTRACT The training program of making compost from agriculture waste was conducted on September 25 th until October 26 th 2009 at Megati Village, district of Selemadeg Timur, Tabanan Regency. This activity aimed at increasing knowledge and skill of participants how to process efficiently the agricultural waste become good quality compost as organic fertilizer. The methods used in this training were: giving conseling, discussion, and practice to make the compost. It involved 16 farmers as participants, 3 speakers as lecturers and several instructurs as assisstants. According to the evaluation result during this activity, the participants were very enthusiatic which can be proved by a lot of questions raised by the participants during conseling session, as well as during the practice. By this training, the participants improved their knowledge and skill to process the agricultural waste into compost efficiently, and ready to use it to improve the soil fertility. From the practice result done in a week, compost has already been used to fertilise plant because it has constant temprature which is 40ºC, then within one month compost has been considered rottening well, characterized by some changes, such as from brown to blackish colour, loose structure, and smooth texture.